Over The Shouler Shot Analysis On The King's Speech Film - Pius Rino Pungkiawan (Sense: Journal of Film and Television Studies, 2022)
The film The King's Speech takes the theme of British work history about Prince Albert's journey to overcome his stuttering problem with a therapist named Lionel Logue who later becomes his best friend. This film has received many awards from various world-class awards, one of which is the Oscar. This study focuses on analyzing the cinematographic aspect of the use of shot over shoulder in the film The King's Speech. Analytical method with interpretive visual with descriptive qualitative research type. The results showed that the use of shot over the shoulder was built in stages with the motivation to show the close friendship between the characters.